Validity of Hemoglobin A1C before 20 weeks of gestation for prediction of gestational diabetes mellitus - Ali Shahriari; Fatemeh Safavi; Maryam Khooshideh; Mohammadali Shahriari (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2020)
Introduction: The diagnosis of gestational diabetes mellitus (GDM) by HbA1c is up to 6.5%, but some studies have declared that the value of 5.7-6.4 % is associated with higher risk of GDM. This study was performed with aim to determine the validity of HbA1c=5.7-6.4% in the prediction of gestational diabetes and to estimate the outcomes of pregnancy. Methods: This co-group study was conducted on 950 pregnant women in Arash Hospital at 2018. All high risk pregnant single tone women aged 18-35 years pregnancies under 20 weeks were included. At first visit, HbA1c test and OGTT 75 g test were performed as gold standard, if the test was negative; test was again performed at 24-28 weeks of gestation. The incidence of diabetes and pregnancy outcomes including: the incidence of preeclampsia, cesarean section, abortion, macrosomia, shoulder dystocia, intrauterine death, fetal growth retardation were compared in cases with HbA1c = 5.7-6.4 and less than 5.6%. Data were analyzed by Stata software (version 13) and student t-test for quantitative variables and Chi-square test for qualitative variables. Univariate and multivariate logistic regression was used to determine the association between HbA1c and variables. P<0.05 was considered statistically significant. Results: The prevalence of diabetes was 39.2% and at the cut-off point of 5.7%, the highest classification of gestational diabetes was observed. At this point, the sensitivity and specificity were 41.33 and 15.92, respectively. The rate of macrosomia was significantly lower in women with HbA1c<5.6 compared to the women with HbA1c= 6.4 – 5. 7 % (p <0.001); however, the rate of cesarean section was significantly higher in this group (p = 0.02). The rate of preterm delivery (p = 0.9), pre-eclampsia (p = 0.2) and shoulder dystocia (p = 1) were not statistically different between the two groups. Conclusion: HBA1C measurement in the first half of pregnancy does not have a high sensitivity for the prediction of gestational diabetes, but it has high specificity.